A Maturity‐level Assessment of Generalised Audit Software: Internal Audit Functions in Australia - Smidt, Louis; Ahmi, Aidi; Steenkamp, Leandi; Van der Nest, D.P.; Lubbe, Dave (Australian Accounting Review, 2018)
The advancement of information technology in today’s technologically driven era has had a significant impact on the way corporate organisations are conducting their business, especially in a developed country such as Australia. Consequently, it is now almost impossible to conduct effective and efficient audits without the use of technology-based tools in control environments that are dominated by big data and increasing volumes of electronic audit evidence. Generalised Audit Software (GAS) is one of the most frequently used technologybased tools available for the internal audit function for tests of controls purposes. The objective of this article is to explore the maturity of the use of GAS by internal audit functions in Australia. The literature review reveals that the use of GAS by internal audit functions globally is still at a relatively low level of maturity, despite the increased adoption of information technology and the generation of big data within organisations. Similarly, the empirical results also confirm the low level of maturity in the use of GAS by internal audit functions in Australia. Only 17.4% of the respondents displayed a high level of maturity with regard to the use of GAS.
Published Article